Design of a novel compact dual band monopole antenna for WLAN - Obma, Jagraphon; Angkawisittpan, Niwat; Suwannata, Nattawoot (Asia-Pacific Journal of Science and Technology, 2017)
This paper presents a new design of the compact dual band monopole antenna for WLAN. The proposed dual band antenna has two parallel spurlines integrated with the conventional monopole antenna. The first operating frequency is designed using the theory of conventional monopole antenna at 2.4 GHz while the second operating frequency is obtained from spurline structures for the frequency of 5.2 GHz. The antenna structure is simulated with the commercial software (CST Microwave Studio) for reflection coefficients and voltage standing wave ratio. The simulated results of reflection coefficients and voltage standing wave ratios are validated with the measured results. Both results are in good agreement. Moreover, the radiation patterns are measured in different planes. The proposed technique can be applied to design dual frequency antennas for other frequency bands.